Discrete Supertetrahedral T5 Selenide Clusters and Their Se/S Solid Solutions: Ionic‐Liquid‐Assisted Precursor Route Syntheses and Photocatalytic Properties. Issue 7 (23rd January 2020) - Wang, Yanqi; Zhu, Zhipeng; Sun, Zhaofeng; Hu, Qianqian; Li, Jianrong; Jiang, Jiang; Huang, Xiaoying
Abstract: Although supertetrahedral T n sulfide clusters ( n= 2–6) have been extensively explored, the synthesis of T n selenide clusters with n >4 has not been achieved thus far. Reported here are ionic‐liquid (IL)‐assisted precursor route syntheses, characterizations, and the photocatalytic properties of six new M‐In‐Q (M=Cu or Cd; Q=Se or Se/S) chalcogenide compounds, namely [Bmmim]12 Cu5 In30 Q52 Cl3 (Im) (Q=Se (T5‐1 ), Se48.5 S3.5 (T5‐2 ); Bmmim=1‐butyl‐2, 3‐dimethylimidazolium, Im=imidazole), [Bmmim]11 Cd6 In28 Q52 Cl3 (MIm) (Q=Se (T5‐3 ), Se28.5 S23.5 (T5‐4 ), Se16 S36 (T5‐5 ); MIm=1‐methylimidazole), and [Bmmim]9 Cd6 In28 Se8 S44 Cl(MIm)3 (T5‐6 ). The cluster compounds T5‐1 and T5‐3 represent the largest molecular supertetrahedral T n selenide clusters to date. Under visible‐light illumination, the Cu‐In‐Q compounds showed photocatalytic activity towards the decomposition of crystal violet, whereas the Cd‐In‐Q compounds exhibited good photocatalytic H2 evolution activity. Interestingly, the experimental results show that the photocatalytic performances of the selenide/sulfide solid solutions were significantly better than those of their selenide analogues, for example, the degradation time of the organic dye with T5‐2 was much shorter than that with T5‐1, whereas the photocatalytic H2 evolution efficiencies with T5‐3 –T5‐6 improved significantly with increasing sulfur content. This work highlights the significance of IL‐assisted precursor route synthesis and the tuning of photocatalytic properties through the formation of solid solutions. Abstract : Fine tweaking . Six heterometallic T5 selenides and their Se/S solid solutions M‐In‐Q (M=Cu or Cd; Q=Se or Se/S) have been solvothermally synthesized by a two‐step method. The T5 selenide clusters, the largest supertetrahedral T n clusters reported to date, show photocatalytic activity that can be tuned according to their constituent components.